Enriching Educators' Repertoire of Appropriate Instructional Methods - Deborah Simpson; Judith (Julie); Judi Rehm; Karen Marcdante (Association of American Medical Colleges, 2010)
Abstract Introduction Educators frequently depend on familiar teaching methods to achieve their educational objectives, reporting limited knowledge of alternative instructional methods. This resource was developed to actively engage educators in learning and applying new instructional methods. Methods During this 1.5-hour card-game exercise, participants begin by either writing one to two objectives derived from their own teaching on a preprinted objective form or drawing from Deck 1, a set of preprinted ACGME-linked objective cards. Then, each participant is dealt at least as many method cards as there are players plus one from Deck 2, which contains more than 75 teaching strategy/instructional method cards. One objective card (from Deck 1 or the player-completed form) is shown. Players each select one method card from their hands and attempt to enthusiastically persuade the other group members that their chosen method is the most suitable to achieve the objective. Participants then vote for the best method presented in that round, receiving 1 point for each vote for their suggested method. Play continues until all participants have had at least one objective reviewed. Upon conclusion of the exercise, each player identifies one to two new methods to pilot. This resource contains a detailed instructor guide and the five exercise components: method cards, objective cards, Write Your Own Objectives form, score sheet, and exercise instructions. Results We have received consistently high ratings for this exercise as evidenced by tabulated descriptive statistics and positive narrative comments focusing on its quality and effectiveness. The exercise has been conducted several times during different faculty development sessions at the Medical College of Wisconsin. Faculty participants on average rated the exercise 6.4 (1 = poor, 7 = excellent) for learning and content, with 93% of participants piloting a new teaching method when meeting 1 month later. The exercise was conducted at the March 2009 CGEA meeting in Rochester, MN, and received an average rating of 6.5 from the participants. It was also presented at the May 2009 Pediatric Academic Society Conference to approximately 40 educators, receiving an average rating of 6.7. Many of the participants requested the list of all the methods and/or the actual exercise itself. The exercise has subsequently been used by other faculty development colleagues with equally positive results. Another Midwestern medical school utilized the exercise with its faculty, rating the exercise 6.1. Discussion This resource has proven to be an engaging and effective approach to expanding educators' repertoires of teaching methods and strategies.